2014
DOI: 10.1371/journal.pone.0093882
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Aortic Calcification and Fracture Risk in Postmenopausal Women in China: The Prospective Chongqing Osteoporosis Study

Abstract: PurposeFractures are associated with cardiovascular diseases in the elderly. The purpose of the present study was to investigate the association between aortic calcification (AC) and the risk of vertebral fractures in postmenopausal Chinese women.MethodsA prospective study with 5 years of follow-up in 1724 postmenopausal women (aged 50 years old and older) was conducted from July 2005 to June 2010. Dual energy X-ray absorptiometry was utilized to evaluate bone mineral density (BMD). Aortic calcification score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
2
19
0
1
Order By: Relevance
“…In a cross-sectional study performed in 624 men and women aged 50–89, severe AAC was associated with higher odds of vertebral fracture, but not with the nonspine fracture (34). Few studies found significant link between severe AAC and overall fracture risk (9,35). These associations were significant only for individuals with severe AAC (>6) and hip fractures comprised a major proportion of the total fracture groups (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a cross-sectional study performed in 624 men and women aged 50–89, severe AAC was associated with higher odds of vertebral fracture, but not with the nonspine fracture (34). Few studies found significant link between severe AAC and overall fracture risk (9,35). These associations were significant only for individuals with severe AAC (>6) and hip fractures comprised a major proportion of the total fracture groups (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In some, but not all, cross-sectional studies, severe AAC was associated with lower bone mineral density (BMD) and higher odds of vertebral and hip fractures (28). In some (89), but not all (1012), prospective studies, severe AAC was associated with higher risk of vertebral and hip fractures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mini-review P. Szulc cohort of postmenopausal Chinese women followed up prospectively for 5 years, severe AAC (>6 on the 24-point scale) was associated with higher risk of vertebral fracture and of major non-vertebral fracture (24). In a cohort of men aged 50 years and older followed up prospectively for 10 years, severe AAC (>6 on the 24-point scale) was associated with higher risk of fracture (25).…”
Section: Vascular Calcification and Fracture Riskmentioning
confidence: 99%
“…Although these conditions commonly co-occur in older adults, growing evidence suggests an association between vascular calcification and skeletal fragility that is independent of age and other shared risk factors. Older adults with the greatest bone loss have the greatest progression of vascular calcification 1,2 and the incidence of cardiovascular (CV) events is greater in women with lower bone mass 3 and in men with higher levels of bone resorption 4,5 . The association between both pathologies also depends on the mechanisms involved in the regulation of bone and CV metabolism 5 .…”
Section: Introductionmentioning
confidence: 99%